Idiopathic Facial Nerve Paralysis Treatment with Acyclovir and Prednisolone Compared with Prednisolone Alone - Selçuk İnanlı; Alper Tutkun; Özmen Öztürk; Çağlar Batman; Cüneyd Üneri; Mehmet Ali Şehitoğlu (Turkish Archives of Otorhinolaryngology, 2001)

(untitled)
In a prospective, controlled and randomized study, we compared the outcome of 42 idiopathic facial paralysis patients treated with acyclovir and prednisolone (n=20) compared with prednisolone alone (n=22). Acyclovir dosage was 2400 mg for 10 days and prednisolone given as a daily dose of 1 mg/kg over the next 12 days. Minimum follow-up was 3 months in all patients. The clinical outcome, neural regeneration and the incidence of sequela were the same in both groups. According to these results we concluded that acyclovir combination to prednisolone is not superior to prednisolone alone in the treatment of idiopathic facial paralysis.